Clinical evaluation of Swedish Interactive Thresholding Algorithm (SITA) in various eye diseases - Goto, Hinako; Okano, Tadashi; Horikoshi, Noriko; Osako, Masahiro; Tamura, Yoko (JAPANESE ORTHOPTIC JOURNAL, 1999)
Swedish Interactive Thresholding Algorithm (SITA) is a new thresholding algorithm for Humphrey Field Analyzer (HFA II) using maximum-likelihood procedure based on normal and glaucomatous visual field models. We evaluated the clinical usefulness of SITA on various diseases other than glaucoma. Subjects are 12 eyes of 12 normals, 23 eyes of 16 cases with ocular hypertension or glaucoma, 23 eyes of 16 cases with retinal disease, and 14 eyes of 8 cases with optic nerve or intra-cranial disease. Program 24-2 of HFA II was performed on each subject using FASTPAC, SITA accurate, and SITA fast. There was a positive correlation between SITA and FASTPAC regarding mean deviation (MD) and pattern standard deviation (PSD) in these diseases. No difference was not found in the reduction of testing time among these diseases. From the comparison of the visual field on each subject, it is thought that the perimetry using SITA is effective for the diseases other than glaucoma.